Life cycle inventory of institutional medium-scaled co-composting of food waste and yard waste in Tropical Country - Chee, Guan Ng; Sumiani Yusoff, (Universiti Kebangsaan Malaysia, 2015)
The main objective of the present study was to provide a comprehensive LCI of medium scale composting of food waste and yard waste at institutional level, based on substance flow analysis (SFA). A secondary objective was to present the composition and assess the quality of the final compost product from composting of typical Asian organic waste (food waste and yard waste). The experiments were designed to represent a batch situation in an institutional medium size composting scenario with input material of food waste mixed with grass clippings and dried leaves. Two composting runs were carried out with the intention to showcase the heterogeneity of organic waste and study the effect of windrow size on the performance of the process. The input and output material were sampled and characterized in order to quantify the substance balance of the process. SFA was performed by means of the mass balance model STAN 2.5 to compute unknown parameters (gaseous emissions). SFAs have been performed for C, N, K, P, Cd, Cr, Cu, Ni and Pb. The composting windrows were fed with 212.4 and 393 kg, respectively. VS content reduction is greater in composting pile with larger size (Run 2). The loss of C during composting was recorded in the range of 0.146-0.166 kg/kg ww. The C losses via leachate were insignificant (0.02% of the total input C). The total N loss during the process was 0.005-0.012 kg/kg ww. The leachate generation was measured as 0.012-0.013 kg/kg ww. The flows of selected heavy metals were assessed. Heavy metals were of minor significance due to low concentrations in the inputs (food waste and yard waste). Heavy metals were found to be released to the atmosphere. However, majority of heavy metals remain in the finished compost. The C/N reduction during the process was in the range of 10-23%. In general, the compost composition was considered to be within the ranges previously reported in literature and thus ready for application in gardening. The LCI presented in the present study can be used as a starting point for making environmental assessments of medium-scale co-composting of food waste and yard waste in tropical environment. No major environmental problems were identified from the process, except for the emissions of GHGs.